CD19: A multifunctional immunological target molecule and its implications for Blineage acute lymphoblastic leukemia. Issue 7 (8th March 2015) - Weiland, Judith; Elder, Alex; Forster, Victoria; Heidenreich, Olaf; Koschmieder, Steffen; Vormoor, Josef
<x xml:space="preserve">Abstract</x> Over the last 20–30 years CD19 has gained attention as a potential target in the therapy of B‐cell malignancies. In particular, targeting CD19 with the bispecific T‐cell engager (BiTE) antibody Blinatumomab and T‐cells modified by chimeric antigen receptors (CAR) has shown promising efficacy in early phase clinical trials for adults and children with precursor B‐cell ALL (BCP–ALL). This review will discuss the rationale behind targeting CD19 in BCP‐ALL and its potential importance in BCP‐ALL signaling pathways. Pediatr Blood Cancer 2015;62:1144–1148. © 2015 Wiley Periodicals, Inc.